A Multidimensional Corporate Social Responsibility Study - Sousa, Maria José (My University, 2014)
Abstract This paper intends to contribute to a better understanding of the corporate social responsibility (CSR) in Portuguese Small and Medium Enterprises (SME)1. In the Portuguese context, where SME represent the majority of companies in the country, the social responsibility is many times confused with philanthropy or patronage, being an occasional practice and not aligned with the company‟s business. Some authors question themselves if some types of actions can be called CSR or if they are only to be seen as altruism or even political actions in order to achieve business success. Supported by several case studies in Portuguese SME2, some of the questions that led this research were: Do the SME studied have CSR practices? If so, what kind of practices? Which is the content and scope of these practices? Are they integrated with the SME business strategies?
Keywords: Corporate Social Responsibility; strategy; SME; companies; internal and external dimensions of CSR